Analysis Of Relationship Between Volume, Speed and Density Based On Greenshield and Greenberg Models A Case Study Of Zainal Abidin Pagar Alam and Imam Bonjol Bandar Lampung. - Naibaho, Theresia Monika; Purba, Aleksander; Karami, Muhammad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
An urban area that has a function as a center of activity in an area certainly affects the high levelof community activity and indirectly causes a high number of movement of people, vehicles andgoods in urban areas.The ability to accommodate traffic flows depends on the physical conditionof a road, both in quality and quantity as well as on the operational characteristics of thetraffic.The purpose of this study is to analyze road characteristics and to determine therelationship between volume, speed and density on the Zainal Abidin Pagar Alam road and theImam Bonjol road in Bandar Lampung. This study uses the Greenshield and Greenberg modelsas a method. This method results that the relationship between velocity and density is linear sothat we can see how the pattern of the relationship between velocity, density and volume is. Theresults of this study obtained the free flow speed for Jalan ZA Pagar Alam for 55 km / hour andfor Jalan Imam Bonjol is 38 km / hour. The actual speed on Jalan ZA Pagar Alam is 28km / hourand on Jalan Imam Bonjol is 30km / hour. Meanwhile, the congestion density found on the ZAPagar Alam road is 931 cur / hour and on Jalan Imam Bonjol is 979 cur / hour. The mostoptimum model is in the Greenberg model for Jalan ZA Pagar Alam because the Greenbergmodel has a determination coefficient value (R2) which is closer to the highest accuracy of 0.98%and the Greenshield model on Jalan Imam Bonjol is because it has a determination coefficientvalue ( R2) which is closer to the highest accuracy of 0.96%.